Elderly female with Autoimmune hemolytic anemia - Anupam Dey (Wolters Kluwer Medknow Publications, 2015)
Autoimmune hemolytic anemia (AIHA) is a rare disease with an estimated prevalence of around 17/100,000. It is often difficult to diagnose and treat AIHA, especially in elderly. A 60-year-old female was admitted with the complaints of low grade fever, on-off for 6 months, progressive fatigue and dyspnea on exertion. She was transfused with three units of blood within these 6 months. Examination revealed pallor, edema, hemic murmur, and palpable liver. Hb was 2.9 gm%, T Bil 5.2 mg/dl, ESR 160 mm, and reticulocyte count 44.05%. Direct Coombs test was positive, anti-nuclear antibody (ANA) and Anti ds DNA were positive. A diagnosis of systemic lupus erythematosus (SLE) with AIHA was considered and patient was transfused with two units of packed red cells and put on steroid (prednisolone) at 1 mg/kg body weight daily. After 3 weeks, her Hb had increased to 10.4 gm% with gross clinical improvement.